Reversible Endoscopic Medial Maxillectomy: Endonasal Approach to Diseases of the Maxillary Sinus - Tepedino,Miguel Soares (2020)
Abstract Introduction The endoscopic access has reduced the morbidity associated with external approaches in diseases of themaxillary sinus. A reversible endoscopic medialmaxillectomy (REMM) is presented as an alternative for treatment of benign maxillary diseases. Objective To describe the REMM technique and report four cases of patients with benign maxillary sinus conditions treated through this approach. Methods The present study was divided into two parts: anatomical and case series. Two cadaveric dissections confirmed the feasibility of the REMMapproach. The same technique was performed on four consecutive patients with benign maxillary sinus disease. Results The cadaveric dissections confirmed wide exposure to the maxillary cavity, preserving the anatomy of the maxillary sinus. In the patient series, one patient presented with an antrochoanal polyp, one had a silent sinus syndrome, one had a chronic maxillary sinusitis secondary to a gunshot, and the last one had an inverted papilloma in the maxillary sinus. In all of the cases, the REMM approach provided excellent access and adequate resection, as well as preservation of the inferior turbinate, nasolacrimal duct, and lateral wall of the nose (including its osteomucosal component). Finally, all of the patients had an uneventful postoperative course. Conclusion The REMM technique is an excellent surgical approach to benign conditions of the maxillary sinus. It has few limitations and appears to be associated with less morbidity than conventional techniques.